Annual and monthly runoff analysis in the Elqui River, Chile, a semi-arid snow-glacier fed basin - Balocchi, Francisco; Pizarro, Roberto; Meixner, Thomas; Urbina, Fernando (Tecnología y ciencias del agua, 2017)
Balocchi, F., Pizarro, R., Meixner, T., & Urbina, F. (November-Â Â December, 2017). Annual and monthly runoff analysis inÂ Â the Elqui River, Chile, a semi-arid snow-glacier fed basin.Â Â Water Technology and Sciences (in Spanish), 8(6), 23-35, DOI:Â Â 10.24850/j-tyca-2017-06-02.Â Â Climate change and its relationship to temperature areÂ Â critical factors affecting glaciers, especially when populationsÂ Â depend on these ice reservoirs. The use of the precipitationrunoffÂ Â coefficient in semi-arid, mountainous regions thatÂ Â are fed by glaciers can lead to important findings aboutÂ Â how glacial melt responds to climate change. This studyÂ Â analyzed 40 years of monthly and annual precipitationÂ Â and runoff data (1970-2009) from four sub-basins of theÂ Â Elqui River (29° 27’- 30° 34’ S and 71° 22’- 69° 52’ W), inÂ Â the Coquimbo region of Chile. The Elqui basin has a rainsnow-Â Â glacial melt regime. The areal average rainfall wasÂ Â estimated using the Thiessen polygon method. GumbelÂ Â and Goodrich probability distribution functions and theÂ Â Log-Normal Probability Density Function (PDF) were usedÂ Â to understand the temporal behavior of precipitation andÂ Â streamflow. The data-time behavior and PP Q-1 coefficientsÂ Â were also analyzed. And the Mann-Kendall (MK) test wasÂ Â used to compare the results. No trends were found for flow,Â Â while a negative trend in rainfall was identified. The summerÂ Â flows were notable, which remained constant. In spite of theÂ Â differences between the PP Q-1 coefficient and the MK test,Â Â the flow clearly does not come from rainfall but rather fromÂ Â glacial melt. Â Â Â